KECERDASAN DAN PERFEKSIONISME PADA ANAK GIFTED DI KELAS AKSELERASI - Pranungsari, Dessy (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
This research was the quantitative research aimed at knowing how far relations between intelligence and perfectionism on the gifted students in the acceleration class. The method of the data collection in this research was the document of the Intelligence Quotient score data (IQ) from the CFIT intelligence test the scale 2 forms ofA & B to be intelligence variable, whereas the scale of perfectionism with the reliability coefficient 0.803 to be the perfectionism variable. Data processing was carried out with the SPSS computation system 13.0 for Wmdows. Try out for the scales were done before. The data analysis, using product moment to examine the correlation between intelligence variable and perfectionism variable, obtained p=0.097 (p>0.05). This showed that there was no correlation between intelligence variable and perfectionism variable on the gifted child in the acceleration class.